Gelcasting of Alumina Ceramics With Gelatin and Carrageenan Gum and Investigation of Their Mechanical Properties - Koçlar, Galip Sarper; Çiftçioğlu, Muhsin; Çiftçioğlu, Muhsin (Izmir Institute of Technology, 2013)
In this study, use of gelatin and carrageenan gum as gel formers in gelcasting process of alumina ceramics was aimed. The effects of each gel former on the mechanical properties of gelcasted alumina ceramics were distinctly investigated. Firstly, an experimental design was made according to pre-experimental studies and researches. In this experimental design, it was determined what the factors should be and how the levels of factors should change. Two groups of gelcasting slips were prepared with alumina powder. One of them was the group that contained gelatin with changing ratios from 3 to 6 wt%. Other was the group that contained carragenan gum with changing ratios from 1 to 2 wt%. Alumina powder amounts of the slips in also each group were the same and changing from 47 to 53 vol%. Furthermore, in order to see the direct effect of each gel former type and amount on mechanical properties and compare the methods of gelcasting and slip casting, alumina slips that contained no gelatin or carrageenan gum were also prepared. Green alumina samples in suitable shapes for mechanical tests were obtained by gelcasting method from the prepared slips. After green samples were dried, half of them were sintered at 1550 oC. Rest of them weren’t subjected to any heat treatment. Green samples in block shape were cut in suitable dimensions for 3-point bending test before they were sintered. Shrinkage and densification ratios of the alumina samples after drying and sintering were measured and calculated. At the end of the mechanical tests applied on green and sintered alumina ceramics, data about change in their bending strength, compressive strength and hardness values due to varying gel amount and sintering were obtained. These data were analyzed, then the obtained results were interpreted. While optimum gel former amount needed for maximum compressive and bending strength of gelatin-gelcasted alumina samples was 5 wt%., this amount for that of gum-gelcasted alumina samples was 1.7 wt%. The effect of alumina solid loading on mechanical properties of gelcasted alumina samples was unclear. After sintering of gelatin-gelcasted alumina samples, the densification reached to a maximum of 95.80%.
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2013
Includes bibliographical references (leaves: 53-55)
Text in English; Abstract: Turkish and English
x, 60 leaves
Keywords: Ceramic materials--Mechanical properties; Aluminum oxide; Oxide ceramics; Gelatin